Klebsiella pneumoniae manipulates human macrophages to acquire iron - Grubwieser, Philipp; Hilbe, Richard; Gehrer, Clemens Michael; Grander, Manuel; Brigo, Natascha; Hoffmann, Alexander; Seifert, Markus; Berger, Sylvia; Theurl, Igor; Nairz, Manfred; Weiss, Günter (Frontiers in Microbiology, 2023)
Background Klebsiella pneumoniae (KP) is a major cause of hospital-acquired infections, such as pneumonia. Moreover, it is classified as a pathogen of concern due to sprawling anti-microbial resistance. During infection, the gram-negative pathogen is capable of establishing an intracellular niche in macrophages by altering cellular metabolism. One factor critically affecting the host-pathogen interaction is the availability of essential nutrients, like iron, which is required for KP to proliferate but which also modulates anti-microbial immune effector pathways. We hypothesized, that KP manipulates macrophage iron homeostasis to acquire this crucial nutrient for sustained proliferation. Methods We applied an in-vitro infection model, in which human macrophage-like PMA-differentiated THP1 cells were infected with KP (strain ATCC 43816). During a 24-h course of infection, we quantified the number of intracellular bacteria via serial plating of cell lysates and evaluated the effects of different stimuli on intracellular bacterial numbers and iron acquisition. Furthermore, we analyzed host and pathogen specific gene and protein expression of key iron metabolism molecules. Results Viable bacteria are recovered from macrophage cell lysates during the course of infection, indicative of persistence of bacteria within host cells and inefficient pathogen clearing by macrophages. Strikingly, following KP infection macrophages strongly induce the expression of the main cellular iron importer transferrin-receptor-1 (TFR1). Accordingly, intracellular KP proliferation is further augmented by the addition of iron loaded transferrin. The induction of TFR1 is mediated via the STAT-6-IL-10 axis, and pharmacological inhibition of this pathway reduces macrophage iron uptake, elicits bacterial iron starvation, and decreases bacterial survival. Conclusion Our results suggest, that KP manipulates macrophage iron metabolism to acquire iron once confined inside the host cell and enforces intracellular bacterial persistence. This is facilitated by microbial mediated induction of TFR1 via the STAT-6-IL-10 axis. Mechanistic insights into immune metabolism will provide opportunities for the development of novel antimicrobial therapies.